Analisis Perbandingan Pengalaman Pengguna dan Kualitas Layanan pada Aplikasi DANA dan OVO Menggunakan Metode User Experience Questionnaire dan Importance Performance Analysis - Syaifullah, Agus; Hamzah, Muhammad Luthfi; Anofrizen, Anofrizen; Syaifullah, Syaifullah (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
The DANA and OVO applications function as online digital wallet or e-wallet platforms. This application has service features such as buying credit, postpaid, electricity bills, insurance, BPJS, parking credit cards which can help users when making online payments. The problems that occur are when the QR transaction balance has been deducted but does not reach the destination, the signal often has problems or errors, bank transaction fees are too high, the security system is weak so user data leaks occur. Therefore, analysis is carried out using the User method. Experience Questionnaire (UEQ) to find out the user's experience after using the application. The Importance Performance Analysis (IPA) method is used to display information about service factors that greatly influence user satisfaction. The IPA method divides questionnaire data into three variables: usefulness, information quality, and service, with a total of 16 questions. From the results of user experience analysis based on 102 responses using UEQ, the user experience on the DANA application is superior to OVO in all aspects of assessment. The results of the IPA analysis show that for the DANA application, there are four items that are the main priority and three items that must be maintained by the manager. Meanwhile, for the OVO application, there are two items that are the main priority and six items that must be maintained.